Heinemann History Britain 1750 to 1900 - Child, John (Heinemann Publishing (Oxford) Ltd, 1995)
Focusing on British history from 1750 to 1900, this book is part of a series which covers the required Study Units at Key Stage 3. Primary and secondary sources are used to present a picture of what life was like in the past.
Keywords: Europe; Great Britain; History